The Mediating Role of Attributions in the Association Between Intimate Relationship Distress and Depressive Symptoms in a Dating Sample of Undergraduate Students. (April 2014) - Shnaider, Philippe; Belus, Jennifer M.; Vorstenbosch, Valerie; Monson, Candice M.; Langhinrichsen-Rohling, Jennifer
The current study investigated the mediating role of depressogenic and intimate relationship distress-maintaining attributions in the association between depressive symptoms and relationship distress in an undergraduate dating sample. Results indicated that taken together, depressogenic and distress-maintaining attributions significantly mediated the association between depressive symptoms predicting relationship distress for women, but not men. Examination of the specific indirect effects revealed that distress-maintaining blame attributions had a significant indirect effect in this association for both men and women. Possible clinical implications for the treatment of depressive symptoms and relationship distress are discussed.